An Investigation into Factors Responsible For Shortage of Professional Guidance and Counsellors in Basic Education in Federal Capital Territory, Abuja, Nigeria. - OLUMIDE, OGUNODE; E., ATTAH, G,.; J., EBUTE, (Researchparks Publishing, 2023)
This study investigated factors responsible for shortage of professional Guidance and Counsellors in Basic Education Schools in Federal Capital Territory, Abuja, Nigeria. The study employed descriptive research survey. The population for this study comprised all the Basic schools in Federal Capital Territory, Abuja. Sample and sampling techniques were employed in selection of sample: Sixty Basic schools were sampled in all the six area councils in in Federal Capital Territory, Abuja. In each of the area council, Ten (10) Basic school were selected and in each of the schools, one Guidance and Counselling teacher was selected by means of simple random sampling technique. The instrument used for collection of data for this study was questionnaire. A self-constructed questionnaire was used to gather data for the study. The questionnaire was titled “Factors Responsible for Shortage of Professional Guidance and Counsellors Questionnaire” (FRSPGCQ). The instrument was validated using content validity while the reliability co-efficient of 0.65 was obtained through test-re-test method. The data collected were analyzed using means and standard deviations for the research questions. The result obtained showed that inadequate funding, poor manpower planning, corruption, shortage of professional Guidance and Counsellors and shortage of higher institutions offering Guidance and Counselling programme and poor motivation of Guidance and Counsellors are the factors responsible for shortage of professional Guidance and Counselling in Basic education schools in Federal Capital Territory, Abuja, Nigeria.